Interferon-induced sterile alpha motif and histidine/aspartic acid domain-containing protein 1 expression in astrocytes and microglia is mediated by microRNA-181a. (24th August 2016) - Jin, Changzhong; Peng, Xiaorong; Liu, Fumin; Cheng, Linfang; Xie, Tiansheng; Lu, Xiangyun; Wu, Haibo; Wu, Nanping
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Sterile alpha motif and histidine/aspartic acid domain-containing protein 1 (SAMHD1), a newly discovered HIV-1 host restriction factor, has been found to be induced by interferons and to be regulated by microRNA-181a (miR-181a). However, the mechanism of interferons-induced SAMHD1 expression is unclear. Design: We hypothesized that interferons induce SAMHD1 expression through Janus kinase–signal transducer and activator of transcription (JAK–STAT) signaling pathways, which is mediated by miR-181a. Methods: We examined the effect of IFN-α and IFN-γ on SAMHD1 mRNA and protein expression, as well as the levels of phosphorylated SAMHD1 and miR-181a in astrocytes and microglia. To determine whether interferons-induced SAMHD1 expression was mediated by miR-181a, we overexpressed or inhibited miR-181a in these cells and exposed them to interferons. We also detected the effect of SAMHD1 and miR-181a on HIV-1 infection in astrocytes and microglia. Results: Both IFN-α and IFN-γ increased SAMHD1 mRNA and protein expression, and reduced miR-181a levels, particularly in microglia. Phosphorylated SAMHD1was not induced by interferons. Overexpression of miR-181a counteracted induction of SAMHD1 expression by interferons, and inhibition of miR-181a mimicked interferons treatment. Inhibition of JAK–STAT signaling pathways resulted in increased miR-181a levels and decreased SAMHD1 mRNA expression. Knock-down of SAMHD1 or overexpression of miR-181a enhanced HIV-1 infection, whereas inhibition of miR-181a reduced HIV-1 infection. However, inhibition of HIV-1 infection induced by IFN-α was not significantly affected by miR-181a and SAMHD1. Conclusion: MiR-181a is an important mediator for interferons-induced SAMHD1 expression in astrocytes and microglia, but not for inhibition of HIV-1 infection induced by IFN-α.